2000
DOI: 10.1086/308913
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar and Circumstellar Optical and Ultraviolet Lines toward SN 1998S

Abstract: We have observed SN 1998S which exploded in NGC 3877, with the Utrecht Echelle Spectrograph (6 − 7 km s −1 FWHM) at the William Herschel Telescope and with the E230M echelle of the Space Telescope Imaging Spectrograph (8 km s −1 FWHM) aboard the Hubble Space Telescope. Both data sets were obtained at two epochs, separated by 19 (optical) and seven days (UV data).From our own Galaxy we detect interstellar absorption lines of Ca II K, Fe II λλ2600, 2586, 2374, 2344, Mg I λ2852, and probably Mn II λ2576, at v LSR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 35 publications
9
56
0
Order By: Relevance
“…A comparison with the SN 1998S spectrum from Bowen et al (2000) reveals that several sets of absorption lines match the SN 2011ht lines, namely, Mg ii (∼λ2800) and Fe ii (∼λ2400, λ2586, and λ2612; Figure 10). An 11 Å shift of the UVOT spectrum (which is within the wavelength accuracy of the instrument) was applied based on the line identifications, so it is possible that the overall blueshift seen in the optical is masked.…”
Section: The Spectra Of Sn 2011htmentioning
confidence: 96%
“…A comparison with the SN 1998S spectrum from Bowen et al (2000) reveals that several sets of absorption lines match the SN 2011ht lines, namely, Mg ii (∼λ2800) and Fe ii (∼λ2400, λ2586, and λ2612; Figure 10). An 11 Å shift of the UVOT spectrum (which is within the wavelength accuracy of the instrument) was applied based on the line identifications, so it is possible that the overall blueshift seen in the optical is masked.…”
Section: The Spectra Of Sn 2011htmentioning
confidence: 96%
“…Bowen et al (2000) concluded that the narrow and variable absorption is a signature of the outflows from the super-giant progenitor of SN 1998S, arising in a dense shell, expanding at about 50 km s −1 (see also Fassia et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…See also Patat et al 2010). To the best of our knowledge, short timescale variations of narrow absorptions are known to this level of detail only for one other object, i.e., the core-collapse, type IIn SN 1998S (Bowen et al 2000). High-resolution spectroscopy of this object has revealed a number of Na i D components within the host galaxy, the bluest of which deepened significantly during the 19 days spanned by the two epochs available, implying a Na i column density increase of 1 dex.…”
Section: Discussionmentioning
confidence: 99%
“…Previous observations of Ca ii absorption in HVCs with bright 21 cm emission have yielded six detections, giving Ca ii/H i ratios of (17 AE 6) ; 10 À9 for Complex A (Schwarz et al 1995), (22 AE 1) ; 10 À9 for Complex C (Wakker et al 1996), (3:3 AE 0:9) ; 10 À9 for Complex M (Bowen et al 2000), (33 AE 4) ; 10 À9 for the Magellanic Stream (Songaila & York 1980), (66 AE 8) ; 10 À9 for the Leading Arm of the Magellanic Stream (West et al 1985), and (270 AE 120) ; 10 À9 for Complex WB (Robertson et al 1991). There are also several Ca ii detections toward extragalactic supernovae in directions with very faint or no 21 cm (d 'Odorico et al 1985'Odorico et al , 1989Meyer & Roth 1991;Vladilo et al 1994;Ho & Filippenko 1995, 1996, which yield very high Ca ii/H i ratios.…”
Section: Methodsmentioning
confidence: 98%